Capillary zone electrophoresis for haemoglobinopathy diagnosis. Issue 1 (26th October 2012) - Borbely, Nicole; Phelan, Lorraine; Szydlo, Richard; Bain, Barbara
Abstract : Aims: Capillary zone electrophoresis (CE) at alkaline pH is increasingly used in haemoglobinopathy diagnosis. We report our evaluation of automated CE, using the Capillarys 2 Flex Piercing instrument, as a routine diagnostic method for the detection of variant haemoglobins and the diagnosis of β thalassaemia. Methods: A Capillarys 2 Flex Piercing instrument with Phoresis software was evaluated in our laboratory over a 6-week period, comparisons being made with high performance liquid chromatography (HPLC) and, for haemoglobin A2 quantification, with microcolumn chromatography. Results: The instrument was easy to use and was suitable for the quantification of haemoglobin A2 . Quantification of A2 was precise and the percentage was stable with ageing of the blood specimen. Results differ among HPLC, CE and microcolumn chromatography and use of an instrument-specific, method-specific reference range is therefore recommended until such time as there is standardisation between methods and manufacturers. Common variant haemoglobins were provisionally identified without difficulty. There are some uncommon variant haemoglobins that are detected by HPLC but not by capillary electrophoresis, but the reverse also occurs. Conclusions: Capillary electrophoresis using a Capillarys 2 Flex Piercing instrument is suitable for haemoglobinopathy diagnosis.